Clinical comparison of salicylic acid peel and LED-Laser phototherapy for the treatment of Acne vulgaris in teenagers. (2nd January 2017) - Alba, Monique Narciso; Gerenutti, Marli; Yoshida, Valquíria Miwa Hanai; Grotto, Denise
Abstract : Acne vulgaris treatments usually cause sensitivity, teratogenicity and bacterial resistance. Investigations of other therapeutic techniques, such as phototherapy, are highly relevant. Thus, we compared the effectiveness of two Acne vulgaris treatments in adolescents: peeling with salicylic acid (SA) and phototherapy. Teens were randomly divided into: group I, treatment with SA peels (10%) and group II, treatment with phototherapy (blue LED and red laser lights). Photographs were taken before and after ten sessions of each treatment, carried out weekly, and compared. To compare the differences between the treatments, the Student t-test was used. P values < 0.05 were considered significant. Both techniques are effective therapies for the treatment of acne in teenagers since the number of comedones, papules and pustules decreased significantly at the end of the session. However, when the two treatments were compared, phototherapy showed a significant difference in reducing the number of pustules. The combined use of red and blue lights due to their anti-inflammatory and wound-healing properties is a more efficient alternative for treating Acne vulgaris in relation to SA and proves more reliable and without side effects, improving the adolescents' skin health.